Pengaruh penerapan community of inquiry menggunakan LINE terhadap keterampilan berpikir kreatif siswa SMA pada materi energi terbarukan - Nurlistia Chandra Kirana; Sri Anggraeni; Sariwulan Diana (Department of Biology Education, Universitas Pendidikan Indonesia, 2021)
Creative thinking skills are needed by someone to face the challenges in the 21st century. A learning model is needed that can facilitate students to hone their creative thinking skills. Science learning must emphasize student activities through inquiry, one of which is the Community of Inquiry (CoI) learning model. Creative thinking skills in this study consist of aspects of fluency, flexibility, originality, and elaboration. This study aims to analyze the effect of implementing the CoI learning model using LINE on high school students' creative thinking skills in renewable energy concept. The method and design used in this study was a quasi experimental non-equivalent control group design. Participants involved in this study consisted of 61 students who were determined by purposive sampling technique with the characteristics of class X MIPA students who have an account and are accustomed to using the LINE application. CoI learning using LINE was applied to the experimental class, while the control class carried out conventional online learning. Sources of research data were obtained from creative thinking test instruments, student response questionnaires, and observation sheets of learning model implementation. The test instrument for students' creative thinking skills was given as a pre-test and post-test. The results of the pre-test data analysis showed that the students' initial creative thinking skills in the control class and the experimental class were the same and were in the low category. After the learning was carried out, the average post-test score of the experimental class was higher than the control class and there was a significant difference in the mean. The N-gain score of the experimental class was included in the moderate category, while the control class was included in the low category. So, it can be concluded that the application of CoI learning using LINE affects creative thinking skills in renewable energy concept.